Pengaruh Jenis Kemasan Terhadap Karakteristik Kimia Tempe Kedelai - Khilyatun Nisak, Yunita; Azizah, Aqqidatul; Amania, Lailatul (Politeknik Negeri Ketapang, 2025)
Tempeh is a traditional food made from fermented soybeans with the help of Rhizopus sp., which is rich in protein. Tempeh packaging refers to the material used to wrap and protect tempeh, ensuring that its quality and safety are maintained. This study aims to determine the effect of different types of tempeh packaging on pH levels, total acid content, and tempeh protein. The study involved six treatments: plastic packaging, young banana leaf packaging, old banana leaf packaging, turmeric leaf packaging, teak leaf packaging, and taro leaf packaging. The results indicate that tempeh in plastic packaging had the lowest pH of 7.2, while the highest total acid content was found in tempeh packaged with old banana leaves (0.42). In protein testing, tempeh packaged with teak leaves, taro leaves, and young banana leaves produced a bright purple color, while tempeh in old banana leaf and turmeric leaf packaging produced a pale purple color. Tempeh in plastic packaging showed a purplish-blue color.